2018
DOI: 10.3375/043.038.0508
|View full text |Cite
|
Sign up to set email alerts
|

Conserving All the Pollinators: Variation in Probability of Pollen Transport among Insect Taxa

Abstract: As concern about declining pollinator populations mounts, it is important to understand the range of insect taxa that provide pollination services. We use pollen transport information acquired over three years in two habitats at Badlands National Park, South Dakota, USA, to compare probabilities of pollen transport among insect taxa and between sexes of bees. Sampling was conducted on 1-ha plots, eight in sparse vegetation (May-October samples; N = 74 surveys) and 12 in wheatgrass prairie vegetation (June-July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The increase we document in mean C in higher-richness plots suggests these also may improve habitat for butterflies and other pollinating insects. Denning and Foster (2018b) observed a correlation between forb and bee diversity on their tallgrass prairie study sites, so the greater forb richness we observed in our extra-high plots may prove attractive to bees, which are arguably among the most important pollinating insects (Larson et al 2018b). Adding forb species was effective in our study, in that these species established, persisted, and even dispersed to other plots during the 10 y since planting.…”
Section: Discussionmentioning
confidence: 49%
“…The increase we document in mean C in higher-richness plots suggests these also may improve habitat for butterflies and other pollinating insects. Denning and Foster (2018b) observed a correlation between forb and bee diversity on their tallgrass prairie study sites, so the greater forb richness we observed in our extra-high plots may prove attractive to bees, which are arguably among the most important pollinating insects (Larson et al 2018b). Adding forb species was effective in our study, in that these species established, persisted, and even dispersed to other plots during the 10 y since planting.…”
Section: Discussionmentioning
confidence: 49%
“…Similarly diverse and unspecialized flower-visitor assemblages were found for Eriogonum pelinophilum, a rare perennial buckwheat found in restricted habitats in western Colorado (Tepedino et al, 2011). Further, the numerous males collected on E. visheri would have primarily been visiting the flowers for nectar and would be expected to carry less pollen than females (Larson et al, 2018).…”
Section: Does Presence Of E Pauciflorum S Tragus or M Officinalis Pollen On Stigmas Influence Achene Weight Or Germination Likelihood?mentioning
confidence: 99%
“…Nearly 88% of plants globally rely on animals (mostly insects) to transport pollen among plants (Ollerton et al 2011). Most pollinators visit flowers to drink the nectar and pollen sticks to their bodies while they drink, but bees actively collect pollen to feed their young, which may explain why they are prolific pollinators in most ecosystems (Larson et al 2018). When we observe a bee visiting a flower, that bee may be drinking nectar, collecting pollen or both.…”
Section: Introductionmentioning
confidence: 99%